Inclusion of Cu nano-cluster 1D arrays inside a C3-symmetric artificial oligopeptide via co-assembly. Issue 48 (23rd November 2015) - Gong, Ruiying; Li, Fei; Yang, Chunpeng; Wan, Xiaobo
Abstract : A specific C 3 -symmetric artificial oligopeptide was designed to form Cu(0) 1D arrays inside the oligopeptide nanofibers. The key feature of this oligopeptide is that the binding sites (triazole groups formed by click reaction) are located at the center, while the three oligopeptide arms with a strong tendency to assembly are located around it. Abstract : A peptide sequence N3 -GVGV-OMe (G: glycine; V: valine) was attached to a benzene 1, 3, 5-tricarboxamide (BTA) derivative via "click chemistry" to afford a C 3 -symmetric artificial oligopeptide. The key feature of this oligopeptide is that the binding sites (triazole groups formed by click reaction) are located at the center, while the three oligopeptide arms with a strong tendency to assemble are located around it, which provides inner space to accommodate nanoparticles via self-assembly. The inclusion of Cu nanoclusters and the formation of one-dimensional (1D) arrays inside the nanofibers of the C 3 -symmetric artificial oligopeptide assembly were observed, which is quite different from the commonly observed nanoparticle growth on the surface of the pre-assembled oligopeptide nanofibers via the coordination sites located outside. Our finding provides an instructive concept for the design of other stable organic–inorganic hybrid 1D arrays with the inorganic nanoparticles inside.